Late hepatitis B reactivation following direct‐acting antiviral–based treatment of recurrent hepatitis C in an anti‐HBc–positive liver transplant recipient. Issue 2 (4th January 2018) - Vionnet, Julien; Pascual, Manuel; Testoni, Barbara; Combet, Christophe; Godat, Sébastien; Vijgen, Sandrine; Aubert, Vincent; Rubbia‐Brandt, Laura; Zoulim, Fabien; Moradpour, Darius
Abstract : Direct‐acting antivirals (DAAs) have changed the landscape of hepatitis C virus (HCV) treatment, but chronic hepatitis C (CHC) remains a leading indication for liver transplantation (LT). Hepatitis B virus (HBV) reactivation has been reported in HBV‐HCV‐coinfected patients treated with DAAs. We report on a case of late HBV reactivation after DAA‐based treatment of recurrent hepatitis C in an antibody against hepatitis B core antigen (anti‐HBc)‐positive LT recipient. (Hepatology 2018;67:791‐793).